Heavy metals in the environment [origin, interaction and remediation] - Bradl, H. B. (Heike B.) (Amsterdam ; Elsevier Academic Press, Boston, 2005)
Excessive levels of heavy metals can be introduced into the environment, for example, by industrial waste or fertilizers. Soil represents a major sink for heavy metals ions, which can then enter the food chain via plants or leaching into groundwater. In Heavy Metal Ions in the Environment, the author looks at where heavy metals ions come from, how they interact with the environment and how they can be removed from the environment - by a process known as remediation. This book serves as a valuable addition to an increasingly important field of study, which is, at present, served by a limited number of archival texts. * Includes comprehensive coverage of heavy metal ions in the environment * Is practical and easy to read * Is suitable for students and researchers in environmental science and environmental or chemical engineering.
CHAPTER 1: SOURCES AND ORIGINS OF HEAVY METALS -- 1. Introduction -- 2. Heavy Metals in Rocks and Soils -- 3. Heavy Metals in Water and Groundwater -- 4. Heavy Metals in the Atmosphere -- 5. Anthropogenic Sources of Heavy Metals -- CHAPTER 2: INTERACTION OF HEAVY METALS -- 1. Analytical Procedures for the Detection of Heavy Metals -- 2. Biogeochemical Processes regulating Heavy Metal Mobility -- 3. Ecotoxicological Effects of Heavy Metals -- 4. Individual Behaviour of Selected Heavy Metals -- CHAPTER 3: REMEDIATION TECHNIQUES -- 1. Introduction -- 2. Physical Remediation Techniques -- 3. Chemical Remediation Techniques -- 4. Phytoremediation of Heavy Metals.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Heavy metals -- Environmental aspects; Electronic books